Description of a new species of Sinocaulus Fairmaire from China (Coleoptera: Dascillidae) - Jin, Zhenyu; Ślipiński, Adam; Wang, Wenkai (Zootaxa, 2015)
A new species of the genus Sinocaulus Fairmaire, 1878, S. truncatus sp. nov., is described from Guizhou, China. Based on the strongly protuberant eyes, the new species is similar to S. omiensis Jin, Ślipiński & Pang, 2013 from Sichuan, but differs from that species in the truncate phallobase of the aedeagus and ventral lobes slightly shorter than dorsal lobe. Distributional data and a key to all four species of Sinocaulus are provided.